Effects of a 5-Year Exercise Intervention on White Matter Microstructural Organization in Older Adults. A Generation 100 Substudy - Pani, Jasmine; Eikenes, Live; Reitlo, Line S.; Stensvold, Dorthe; Wisløff, Ulrik; Håberg, Asta Kristine (Frontiers in Aging Neuroscience, 2022)
Aerobic fitness and exercise could preserve white matter (WM) integrity in older adults. This study investigated the effect on WM integrity of 5 years of exercise intervention with either supervised moderate intensity continuous training (MICT), high intensity interval training (HIIT) or following the national physical activity guidelines. A total of 105 participants (70-77 years at baseline) participating in the randomized controlled trial Generation 100 Study, volunteered to take part in this longitudinal 3T MRI study. The HIIT group (n=33) exercised for 4x4 minutes intervals at ~90% of peak heart rate twice a week, the MICT group (n=24) exercised continuously for 50 minutes at ~70% peak heart rate twice a week while the control group (n=48) followed the national guidelines of ≥30 minutes of physical activity almost every day. At baseline and at 1-, 3- and 5-year follow-ups, diffusion tensor imaging (DTI) scans, cardiorespiratory fitness (CRF) measured as peak oxygen uptake (VO2peak) with ergospirometry, and information on exercise habits were collected. There was no group*time or group effect on WM fractional anisotropy (FA) or WM mean diffusivity (MD) at any timepoint during the intervention. Across all groups, there was a positive association between CRF and FA and negative association between CRF and MD at baseline and 1-year follow-up. Exercise intensity was associated with MD, but not FA, at 1- and 3-year follow-up. There was no association between exercise duration and FA or MD. Despite the lack of group*time interaction or group effect, both higher CRF and exercise intensity were associated with better WM integrity at baseline and 1-year, but not for the entire duration of the intervention study. Different aspects of exercising affected WM metrics and WM tracts differently with the greatest and most overlapping effects in the corpus callosum. The current study indicates that high CRF and exercise intensity are protective of WM integrity in aging.